Accediendo a distintas formas de candidatura: un análisis sobre los usos de plataformas digitales para buscar empleo - Mola Zanatti, Gabriel Loret de (2022)
For some decades, changes have been experienced in society with respect to the technologies that are used, as well as in the way they are used by people. Taking this into account, together with the fact that both unemployment and laws that are not made to support job seekers have increased, we have begun to see a greater number of digital platforms being used to find employment. That is why this research is focused on studying the strategies that people use when seeking employment through digital platforms in the state of Rio Grande do Sul, especially focused on the city of Pelotas. For that there have been two study approaches, the same people who seek employment and the platforms used. To learn more about the first, semi-structured scripted interviews have been carried out, and for the second, the way in which the platforms are used and managed has been observed. Thus, these search tools have been divided into two groups: first, there are those managed by the State, where SINE Pelotas, a Facebook page, and SINE Fácil, an application made by the government, are found. On the other hand, there are the platforms managed by people or companies, where the Empregos Pelotas Facebook group and different WhatsApp groups can be found. Along with that, the labor context created by the 2017 reform and the new contract modality called carteira verde e amarela have been analyzed. Two other points have been investigated in the same way. On the one hand, there is the feeling that people have that anything can be found on the Internet quickly and easily, although little by little they realize that it is not totally certain. On the other hand, there is the responsibility when looking for a job, since some people think that it is something totally individual, while another part says that it is a joint responsibility between the individual and the State. Although despite that they see that state assistance as an aid or favor that is done to citizens and not as a right.